2018
DOI: 10.3390/ani8060085
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Emotional Valence in Wild Boar (Sus scrofa) Calls

Abstract: Simple SummaryAnimal welfare today is assessed based on both the physical and mental health of animals. However, measuring animal mental health, which includes emotions (i.e., short-term positive or negative reactions to specific events), remains a challenge. Since animals are known to use vocalizations to communicate their emotions to their peers, knowledge about how the structure of vocalizations changes with emotions could be very useful in order to develop noninvasive indicators for assessing animal welfar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 46 publications
4
26
1
2
Order By: Relevance
“…Interestingly, we did not find significant differences in the other measured acoustic parameters between positive and negative contexts, which differs from recent studies 22,37,38 . There are several non-mutually exclusive explantions why the outcomes differ among studies: firstly, the emotional valence experienced by indiviudals may not have differed enough to be reflected in the measured acoustic parameters.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we did not find significant differences in the other measured acoustic parameters between positive and negative contexts, which differs from recent studies 22,37,38 . There are several non-mutually exclusive explantions why the outcomes differ among studies: firstly, the emotional valence experienced by indiviudals may not have differed enough to be reflected in the measured acoustic parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…Secondly, the experimental design of previous studies differed from ours in several other aspects, including day of recording, number of individuals present during recording and the functional relevance of the context e.g. social isolation, startling and aggression as negative contexts and food anticipation and affiliative interactions as positive contexts 22,28,37,38 . Thirdly, it may be that the calls produced here were influenced more by unmeasured factors than the valence of the contexts.…”
Section: Discussionmentioning
confidence: 87%
“…Secondly, this classification decline could relate to the within-heifer vocal variability which likely arose from cattle being exposed to different emotionally loaded contexts. Changes in emotional state have been shown to result in modulations of vocalisations 3,31,33,38 , with a growing body of literature on vocal indicators of emotion in pigs 39,40 , horses 38,41 and goats 31,42 . Thus, in addition to identity cues, vocal cues of emotion should be studied in cattle high-frequency calls.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis confirmed that vocalizations of wild boars could be broadly categorized into four classes listed above. Wild boar calls also contain information on emotional valence [137]. Animals were given three different treatments (anticipating a food award, affiliative interactions and antagonistic interactions) and had their calls recorded during these treatments.…”
Section: Pigsmentioning
confidence: 99%
“…Screams and squeals tended to be produced during negative interactions, and grunts were associated with positive situations. Maigrot et al [137] also used energy quartiles, duration, formants and harmonicity in order to infer emotional valence for the different call types and situations.…”
Section: Pigsmentioning
confidence: 99%